(untitled) (EAAE Annual Conference Proceedings, 2019)
Drafting and designing in architecture involve an iterative process of testing and comparing architectural thoughts and ideas. The goal of this iterative process is to find the best of several possible solutions, at each stage of the design process. To bring these architectural thoughts and ideas to reality designers need tools. Tools for discussing ideas and writing, sketching, plan drawing and model making for explaining, documenting and testing thoughts. But do the users of these tools, the designers, really know how these tools work or do the designers use these tools only out of habit? Some tools are already known for how they transport ideas, other tools are used out of behaviour without understanding their deeper impact on transporting thoughts and generating new ideas.